Effects of Koumiss on Intestinal Immune Modulation in Immunosuppressed Rats - Li, Qinyu; Zhang, Chunjie; Xilin, Tuya; Ji, Mingyue; Meng, Xiangxi; Zhao, Yulian; Siqin, Bateer; Zhang, Na; Li, Minhui (Frontiers in Nutrition, 2022)
Koumiss is a traditional fermented dairy product with health and medicinal benefits. It is very popular in the Inner Mongolia Autonomous Region of China. The results of relevant studies have shown that koumiss can regulate the gastrointestinal environment, improve the absorption of nutrients, improve the body's intolerance to lactose, enhance the body's immunity, prevent scurvy and atherosclerosis, and aid in the treatment of tuberculosis. However, there are no systematic reports on the effects of koumiss on immunity. In this study, we aimed to decipher the effects of koumiss on intestinal immune modulation. We used liquid chromatography-tandem mass spectrometry analysis to determine the composition of Koumiss. Using Compound Discoverer software, we compared the mass spectrometry data with the compound information in the online databases ChemSpider and mzCloud to intelligently identify the main chemical components of koumiss. Additionally, we used Mass Frontier small molecule fragmentation libraryTM to determine the structure of fragment ions. A total of 21 components were identified, which clarified the chemical basis of koumiss. These 21 compounds were then used to perform molecular docking with immune-related targets, such as TNF, IL2I, L10, etc. The results indicated good docking activity between most of the compounds and the targets. Then, an immunosuppressive rat model was used to determine the therapeutic effect of koumiss. The results of this study showed that koumiss could, to a certain extent, correct the atrophy of the thymus and spleen in immunosuppressed model rats. The number of leukocytes, lymphocytes, and the CD4+/CD8+ ratio of peripheral blood lymphocytes was also increased. In addition, it could effectively improve the structure of the small intestinal mucosa, which shows that koumiss has a positive effect on the intestinal immune function of immunosuppressed rats. These findings provide an experimental basis for the development and utilization of koumiss as a therapeutic product.